2017
DOI: 10.1051/ocl/2017040
|View full text |Cite
|
Sign up to set email alerts
|

Pequi: a Brazilian fruit with potential uses for the fat industry

Abstract: -Pequi is a native fruit from Brazil, found in the Amazon, Caatinga, Cerrado and Atlantic Rain Forest regions. It is one of the main plants with great potential for sustainable use in Central Brazil. Among 16 species comprising Caryocar genus, three are highlighted: C. brasiliense, C. villosum, and C. coriaceum, of economic importance for families in small communities of Brazilian Cerrado. They are generally organized in cooperatives and use the leaves for preparing medicinal extracts, and the fruits for culin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
(25 reference statements)
0
19
0
4
Order By: Relevance
“…On order to expand the consumer market, it is necessary to develop new products with these fruits, e.g., jams, frozen pulps, cookies, food bars, ice cream, enriched flour, etc. (Carmo et al, 2012;Dias et al, 2003;Guedes et al, 2017;Dliveira et al, 2016;Santos & Silva, 2012;Silva et al, 2014a). Large amount of wastes, such as husks and seeds are discarded during the processing of fruits, and there is very little information on the exploitation of these by-products, thus, requiring further characterization.…”
Section: Introductionmentioning
confidence: 99%
“…On order to expand the consumer market, it is necessary to develop new products with these fruits, e.g., jams, frozen pulps, cookies, food bars, ice cream, enriched flour, etc. (Carmo et al, 2012;Dias et al, 2003;Guedes et al, 2017;Dliveira et al, 2016;Santos & Silva, 2012;Silva et al, 2014a). Large amount of wastes, such as husks and seeds are discarded during the processing of fruits, and there is very little information on the exploitation of these by-products, thus, requiring further characterization.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, with pequi (Caryocar brasiliense) and buriti (Mauritia flexuosa L.) fruits, which are used in the region with different purposes such as human and animal feeding [14,15] , cosmetic and medicinal uses [16] . The fundamental importance in its composition is the abundance in unsaturated fatty acids, with the predominance of oleic acid, between 50-80% in mass, and also, the presence of tocopherols and carothenoids [11,14,15] . They have proved to efficiently plasticize starch and enable fabrication of films by casting [2,3,7,11] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the authors report that the composition of pequi oil may have potential application in the food industry (i.e., less expensive chocolate substitute upon fractionation) and can be used without fractionation or hydrogenation for frying and cooking because of its low content of polyunsaturated fatty acids and a high content of oleic acid. Guedes et al (2017) reported that pequi oil is a source of POP, a TAG of great interest in the food industry. Its high contents of C18:1 and C16:0 is interesting for the food industry, either for cosmetic or oleochemical uses, and the TAG composition indicates its potential use as cocoa butter substitute.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…However, other authors describe pequi as a popular denomination for the fruits of C. brasiliense, which grows in the Central-West Region of Brazil and the western part of the state Minas Gerais; while "piqui" would be considered the fruits of C. coriaceum, which grows in northeastern Brazil; and "pequiá" the fruits of C. villosum, which grows in the Amazon Region (Geocze et al, 2013;Costa et al, 2011;De Oliveira et al, 2010;Lima et al, 2007;Segall et al, 2006;Marx et al, 1997). These three species represent the main source of income for many small communities in Brazil (Leite et al, 2017;Guedes et al, 2017;Figueiredo et al, 2016;Costa et al, 2011;De Moraes Cardoso et al, 2013;Marx et al, 1997).…”
Section: Introductionmentioning
confidence: 99%